A Comparative Study of “Fetus” in the Contemporary & Islamic Shari’ah Perspective - Khan, Janas; Najm ul Hasan; Badshah Rehman (Journal of Islamic and Religious Studies, 2019)
Allah (SWT) dignified human beings among all the creatures and made these (creatures) all subjugated to men. Allah says in the Holy Qur’ān: (He is such a Lord who has created all the things in the universe for you). The beginning of human generation is traced back to the miraculous birth of Adam (A.S), and Allah entrusted their survival in their physical bodies in the process of fusing the male and female gametes in the womb of mother. And new offspring are born undergoing many developmental stages. The Holy Qur’ān has mentioned all the stages of the human being like: its creation started from dust, then from seamen, then a clot, then from a flesh (Al- Qur’ān, 22:5). The same are described by modern medical sciences. The medical sciences also describes it in details that how a “fetus” is created and the process which it passes through. This article discusses how the “Fetus” is described in Islamic Sources, modern medical sciences and what are the similarities between these two?